2019
DOI: 10.1029/2019jd030882
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Supercooled Drizzle at Temperatures Below −25 °C Observed at McMurdo Station, Antarctica

Abstract: The rarity of reports in the literature of brief and spatially limited observations of drizzle at temperatures below −20 °C suggest that riming and other temperature‐dependent cloud microphysical processes such as heterogeneous ice nucleation and ice crystal depositional growth prevent drizzle persistence in cold environments. In this study, we report on a persistent drizzle event observed by ground‐based remote sensing measurements at McMurdo Station, Antarctica. The temperatures in the drizzle‐producing clou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
55
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 25 publications
(66 citation statements)
references
References 82 publications
(126 reference statements)
10
55
1
Order By: Relevance
“…Yet the radiative cooling (Figure 3b3) is too weak to drive sufficient instability to generate turbulence by the end of the simulation. These results are similar to the model sensitivity tests in Silber, Fridlind, et al (2019) where N c was 10 cm −3 or less (see their fig. S5).…”
Section: A Link Between Small Aerosol Particles and Nonturbulent Lbcssupporting
confidence: 91%
See 4 more Smart Citations
“…Yet the radiative cooling (Figure 3b3) is too weak to drive sufficient instability to generate turbulence by the end of the simulation. These results are similar to the model sensitivity tests in Silber, Fridlind, et al (2019) where N c was 10 cm −3 or less (see their fig. S5).…”
Section: A Link Between Small Aerosol Particles and Nonturbulent Lbcssupporting
confidence: 91%
“…To illustrate the impact of aerosol particle sizes on cloud lifecycle, we utilize the Distributed Hydrodynamic Aerosol and Radiative Modeling Application (DHARMA) large‐eddy simulation model (Stevens et al, 2002). We use a model configuration following Silber, Fridlind, et al (2019), which is to our knowledge the only reported observationally grounded modeling case study of supercooled LBC initiation and evolution in an elevated, stable layer, representing a plausible scenario over both poles. We use periodic lateral boundary conditions on a grid size of 1 km ( x ‐axis) × 1 km ( y ‐axis) × 10 km ( z ‐axis) with a 50‐m horizontal and 25‐m vertical mesh between 500 and 2,000 m, linearly stretched above and below.…”
Section: A Link Between Small Aerosol Particles and Nonturbulent Lbcsmentioning
confidence: 99%
See 3 more Smart Citations